Beyond Fragmentation: Challenges of the World of Work in the Face of Ongoing Productive Restructuring (Global Journal of Human-Social Science, 2023)
This article seeks to establish a debate about the contradiction in the current situation of the world of work: the objective force of working class, including the absolute and relative growth of the number of jobs around the world, in parallel with its fragmentation and the development of new modalities and divisions in the world of work, such as the most recent case of uberization. In this sense, it resumes the debates of "end of work", the fragmentation in the neoliberal period, the inflection promoted in 2008, during the financial crisis, in order to develop the analysis of what we call a new productive restructuring, which has been taking place in the current period and needs to be mainly analyzed if we want to understand the trends in the world of work and its challenges.
Keywords: work; productive restructuring; uberization; economic crisis; productive work